REPORT OF EXPERIENCE IN THE PROMOTION OF MEN'S AND WOMEN'S HEALTH FOR PROFESSIONALS IN A PRIVATE COMPANY IN PRESIDENTE PRUDENTE (International Seven Journal of Health Research, 2024)
Introduction: In order to prevent serious consequences, it is imperative to cultivate health care as a primary life habit. The adoption of routine exams and preventive measures is instrumental in preventing the onset of diseases, enabling treatment in its initial phases.  Such an approach not only amplifies the prospects for a cure, but also promotes a remarkable improvement in quality of life and well-being. Thus, informative lectures in order to guide the general population are extremely important for prevention and health promotion in the same.  Taking advantage of the dates of campaigns in the health area, Pink October and Blue November, a lecture was held for employees at the private company Arenales in Presidente Prudente.